1986
DOI: 10.1002/bjs.1800730821
|View full text |Cite
|
Sign up to set email alerts
|

Bile peritonitis after removal of T-tubes from the common bile duct

Abstract: Bile peritonitis can occur when a T-tube is electively removed from the common bile duct, but this is regarded as a rare complication. Plastic T-tubes are known to increase the risk and should not be used. Latex rubber T-tubes are preferred but the complication can still occur. We present three patients with this complication despite the use of a latex T-tube. A questionnaire was sent to 107 surgeons in the South East Thames Region. The replies showed that the complication is far more common than generally rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 7 publications
2
30
0
3
Order By: Relevance
“…These may be displacement, biliary sepsis, thromboembolism, electrolyte and fluid losses, wound infections, pancreatitis and obstructive jaundice [1][2][3][4][5][6]. Biliary leaks have been shown to occur at the time of tube removal or at cholangiography [8] which may progress to intraperitoneal collections, external fistulae or even peritonitis [9][10][11]. The CBD may even be traumatized at the time of removal [13] with possible fibrosis and stricture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These may be displacement, biliary sepsis, thromboembolism, electrolyte and fluid losses, wound infections, pancreatitis and obstructive jaundice [1][2][3][4][5][6]. Biliary leaks have been shown to occur at the time of tube removal or at cholangiography [8] which may progress to intraperitoneal collections, external fistulae or even peritonitis [9][10][11]. The CBD may even be traumatized at the time of removal [13] with possible fibrosis and stricture.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these patients had intraperitoneal collections and the other biliary peritonitis. Bile leaks following removal of the T tube are well documented in literature and although many reasons have been elaborated to try to explain them including choice of material [9,29,30] shape of the T tube [9,31] suture material, [10,28,33,34] surgical technique [35] and the time of removal [11,36] no consistent opinion has been found to hold true in all studies. Thus the actual cause still probably remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 However, prospective trials involving latex T-tubes have also shown cases of bile peritonitis after their removal. 7 It is considered safe to remove latex T-tubes at 7-10 days. 7 However, other authors prefer to leave latex T-tubes in for 21 days.…”
Section: Discussionmentioning
confidence: 99%